Study of managing and developing procedures to calculate the retail packaging waste in New Zealand : a thesis presented in partial fulfilment for the degree of Master of Technology in Packaging Technology at Massey University, Palmerston North, New Zealand - Sheridan, Carl (Massey University, 2003)
The purpose of completing this research is to develop a system that will estimate the total volume of retail packaging in our waste streams. The research also outlines the procedures that are required in order to complete the project in future years. The objectives of the project were to complete a thorough investigation into the following fields of literature; Packaging Fundamentals, Sampling Statistics, Regression Analysis and project management to assist in developing a sound methodology to collect data. Woolworths, Pak N Save, The Warehouse and Liqour King stores were used, as it was believed that these stores would most fairly represent the retail market. The Warehouse in general merchandise, the 2 grocery stores as the food market and the bottle store as one of the foremost users of packaging innovation in the retail market. The largest step of this project was collecting the data. Unfortunately not each piece of retail packaging can be assessed so this project was implemented to rationalise this sample to an accurate and reliable representation of the retail market. Then using a simple net gross weight methodology assess a proportion of the packages to develop conversion equations. Once the conversion equations were developed then these could be applied to all the packages. Secondary Packaging was also assessed but using a slightly different process that investigated the recycling of cardboard from all the stores. This information can then be extrapolated up to represent the complete and entire retail market. This was done on a market share basis. For example Woolworths represent 30% of New Zealand's grocery market. Therefore the weight and volume of packaging from that store could be extrapolated up to represent the complete grocery market. From this, a procedures manual and a future plan was outlined in order to maintain up to date information.
Keywords: Packaging Materials; Sampling (Statistics); New Zealand; Packaging waste